Classification models of students' moods during an online self-assessment test. (10th April 2009) - Moridis, Christos N.; Economides, Anastasios A.
A student's emotional state is crucial during learning. When a student is in a very negative mood, learning is unlikely to occur. On the other hand, a too-positive mood can also impair learning. Thus a key issue for instructional technology is recognising the student's mood, so as to be able to provide appropriate feedback. This paper introduces student's mood models during an online self-assessment test. Two models were evaluated using data emanating from experiments with 153 high school students from three different regions of Greece. The results confirm the models' ability to estimate a student's mood.